2-D and 3-D image registration for medical, remote sensing, and industrial applications - Goshtasby, Ardeshir (John Wiley & Sons, 2005)
"This comprehensive book provides the revant theories and underlying algorithms needed to master the basics of image registration and to discover the cutting-edge techniques used in medical applications, remote sensing, and industrial applications." "This book will serve as an excellent text for classes in image registration, as well as a supplementary textbook in image processing, computer vision, computer graphics, and medical imaging."--Jacket